Peran Mahasiswa KKN 144 UINSU dalam Membangun Masyarakat yang Religius dan Berbudaya melalui Tabligh Akbar dan Inisiatif Pembuatan Tong Sampah: Studi Kasus di Desa Marbau Selatan Kecamatan Marbau Kabupaten Labuhan Batu Utara - Tanjung, Tajuddin; Hasibuan, Intan Syahdila; Jannah, Miftahul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The village environment also lost some of its cleanliness and health. On the side of the road and in the yard of the homeowner's house, rubbish is strewn everywhere. This situation inspired the team to carry out KKN activities in making brick trash cans as a strengthening of the community's culture of clean and healthy living. The village head, village officials and other community members participated in this activity. Local people believe this is necessary to keep the village environment clean and healthy. On the other hand, the community also needs education about the benefits of cultivating a culture of healthy living by disposing of waste properly and trying to turn waste into benefits for the environment. This study uses an implementation approach. The aim of this community service project is to support the people of Marbau Selatan Village, Marbau District, and North Labuhan Batu Regency in maintaining a clean and healthy lifestyle. This research resulted in that the community service event with the theme